Adverse Impact of Venous Thromboembolism on Patients with Cancer - Arora, Mili; Wun, Ted (Seminars in Thrombosis and Hemostasis, 2014)
Venous thromboembolism (VTE) is a common complication of malignancy. This is related to the underlying cancer and thrombogenic effects of various therapies. Compared with VTE in patients without malignancies, cancer-associated thrombosis is associated with increased mortality, recurrence, and bleeding while on anticoagulants. These worse outcomes are due to a complex interplay between the underlying cancer, host response, antitumor therapies, and interactions between anticoagulants and cancer drugs. Primary prevention of VTE may decrease morbidity and possibly even improve cancer-related survival, but studies to date have not clearly identified a patient population that might be of most benefit nor consistently shown a survival benefit to anticoagulation.
Keywords: venous thromboembolism; cancer; chemotherapy; anticoagulation; survival; bleeding